2002
DOI: 10.1038/sj.bjc.6600030
|View full text |Cite
|
Sign up to set email alerts
|

Changes in psychological distress after cancer genetic counselling: a comparison of affected and unaffected women

Abstract: This study sought to examine changes in psychological distress following cancer genetic counselling. Women attending a family cancer clinic completed questionnaires before their appointment and at 2 weeks, 6 months and 12 months after their appointment. Twenty-six women were at low risk of developing breast or ovarian cancer, 76 were at moderate risk, 46 were at high risk and 46 women had previously had breast or ovarian cancer. All groups were compared with regard to measures of anxiety, depression, general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
3
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 31 publications
12
109
3
1
Order By: Relevance
“…This is comparable to the findings in other samples of women prior to genetic risk counselling using the same measure and threshold (Cull et al, 1999 and to published data from the general population (Goldberg and Williams, 1988). Mean scores on the Cancer Worry Scale were similar to those reported in women prior to genetic risk counselling by Watson et al (1998) and Brain et al (2000) and slightly lower than those reported by Hopwood et al (2001) and Bish et al (2002).…”
Section: Discussionsupporting
confidence: 77%
“…This is comparable to the findings in other samples of women prior to genetic risk counselling using the same measure and threshold (Cull et al, 1999 and to published data from the general population (Goldberg and Williams, 1988). Mean scores on the Cancer Worry Scale were similar to those reported in women prior to genetic risk counselling by Watson et al (1998) and Brain et al (2000) and slightly lower than those reported by Hopwood et al (2001) and Bish et al (2002).…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, these outcomes are comparable to previous reports on PPC and STAI outcomes for in-person oncogenetic counselling. 1,13,[22][23][24][25] The mean anxiety level of online patients both before and after counselling was significantly lower than of controls. This might be an indication that patients who choose for online counselling are in general less anxious in nature than patients who choose for in-person counselling.…”
Section: Discussionmentioning
confidence: 85%
“…We do not have access to data on how many of the participants actually went ahead with genetic testing, or their actual test results. The primary outcome measure was anxiety, the reduction of which is regarded as a key counselling objective (Shaw et al, 1999;Brain et al, 2000;Meiser and Halliday, 2002) and a number of evaluations of genetic counselling for familial cancer have identified the pre-and postcounselling assessment of generalised anxiety as a main outcome measure (Cull et al, 1998Julian-Reynier et al, 1999;Brain et al, 2000;Kent et al, 2000;Bish et al, 2002;Bowen et al, 2004). Evidence from systematic reviews suggests that, overall, genetic counselling has the effect of significantly reducing patients' anxiety levels, at least in the short-term (Meiser and Halliday, 2002;Butow et al, 2003;Braithwaite et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The short version produces result comparable with the full state scale and has been used in other genetic counselling research (Miedzybrodzka et al, 1995;Bish et al, 2002). We also included the Hospital Anxiety and Depression Scale (HADS; Zigmond and Snaith, 1983), which gives separate measures of anxiety and depression assessed over the past week (range of scores from 0 to 21, seven items for anxiety and seven for depression).…”
Section: Data Collectionmentioning
confidence: 99%